2013
DOI: 10.3109/01676830.2013.814687
|View full text |Cite
|
Sign up to set email alerts
|

Visual Function and Quality of Life in Patients Who Had Undergone Eye Removal Surgery: A Patient Survey

Abstract: This survey increases our knowledge of aspects of vision-related health status following ocular pathology or trauma that requires eye removal, and may enable improved pre-operative patient counselling. Effects on peripheral vision may be noted most significantly, but the majority can continue normal activities with little difficulty. Overall improvement in comfort and appearance occurs in most patients, although feelings of self-consciousness are common.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…These results are similar to those found in the present study. 53 comprised 36 patients treated by evisceration (64%) or enucleation (36%) for a variety of conditions other than malignancy (eg, trauma, glaucoma, and retinal detachment). Pathology in the fellow eye was present in 28% of patients, with visual loss in several of these.…”
Section: The Collaborative Ocular Melanoma Study Groupmentioning
confidence: 99%
“…These results are similar to those found in the present study. 53 comprised 36 patients treated by evisceration (64%) or enucleation (36%) for a variety of conditions other than malignancy (eg, trauma, glaucoma, and retinal detachment). Pathology in the fellow eye was present in 28% of patients, with visual loss in several of these.…”
Section: The Collaborative Ocular Melanoma Study Groupmentioning
confidence: 99%
“…When asked if loss of the eye had affected various day‐to‐day activities, 80% reported ‘no effect’. A more recent survey found that loss of an eye did not significantly impede normal daily activities, including driving, despite impairment of peripheral vision and judgement of distance .…”
Section: Discussionmentioning
confidence: 98%
“…The tumor registry in 2012 reported 763 cases of Rb. 11 We enrolled patients who had undergone bilateral eye removal to review their HQL in 2020. This study was approved by the Institutional Research Board (IRB: 1471).…”
Section: Methodsmentioning
confidence: 99%
“…7,8 However few publications evaluate HQL in children and young adults who have undergone removal of both eyes. 6,10,11…”
Section: Introductionmentioning
confidence: 99%